Pengaruh Penetapan Harga Dan Kualitas Pelayanan Oleh Agen Telur UD. Enggal Jaya Terhadap Kepuasan Peternak Ayam Layer Di Kabupaten Kediri - Agung Imam Utomo; Sumarji Sumarji; Supriyono Supriyono (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
Egg marketing is the final process of a business activity for breeding chicken eggs where farmers or producers convey the results of their production to consumers with the help of marketing institutions. The intense competition in the field of egg marketing is characterized by many egg agents that offer a variety of cooperation with various advantages. The level of satisfaction of farmers will determine the sustainability of business cooperation with egg agents. The purpose of this study is (1) knowing how the influence of pricing by egg agents UD. Enggal Jaya on the satisfaction of chicken farmers layer, (2) know how the influence of service quality by egg agents UD. Enggal Jaya on the satisfaction of layer chicken farmers and (3) know how the effect of determining the price and quality of service by egg agents UD. Enggal Jaya for the satisfaction of chicken farmers. The data analysis method used is multiple linear regression analysis. The conclusion of this study is that pricing has no positive and insignificant effect while service quality has a positive and significant effect on the satisfaction of layer chicken farmers, pricing and services simultaneously affect the satisfaction of layer chicken farmers.